2020
DOI: 10.14421/pjk.v13i2.1841
|View full text |Cite
|
Sign up to set email alerts
|

Examining Communication Mediation Model on Youth Online Political Engagement

Abstract: Using a communication mediation model, the present study tested the influencing factor of social media utilization on the political engagement on social media. Through O-S-O-R model proposed by McLeod, Kosicki, and McLeod, this study tested the correlation between pre-exposure (motivation) – Stimulus (media social use) – post-exposure orientation (political efficacy) – Response (political engagement) in the context of Chinese youth of Singkawang. By analyzing the Pearson correlation and linear regression of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Exposure to news media (especially television media, newspapers and news websites) further enhances greater political trust. On the other hand, another study found that the use of social media did not have a positive and significant effect on political trust (Azis et al, 2020).In fact, over the last three decades, consumption of news media about the crisis led to greater public distrust of government, which in turn triggers the feeling that the political system that is run is unresponsive.Negative news about unpopular government policies and uncivilized behavior of political elites can reduce and erode trust in government (Moy, 2008).…”
Section: Consumption Of Media Coverage and Political Trustmentioning
confidence: 98%
“…Exposure to news media (especially television media, newspapers and news websites) further enhances greater political trust. On the other hand, another study found that the use of social media did not have a positive and significant effect on political trust (Azis et al, 2020).In fact, over the last three decades, consumption of news media about the crisis led to greater public distrust of government, which in turn triggers the feeling that the political system that is run is unresponsive.Negative news about unpopular government policies and uncivilized behavior of political elites can reduce and erode trust in government (Moy, 2008).…”
Section: Consumption Of Media Coverage and Political Trustmentioning
confidence: 98%